A multispecies model for the transmission and control of mastitis in dairy cows - White, L; Schukken, Y; Lam, T; Medley, G; Chappell, M (Cambridge University Press, 2002)
Mastitis in dairy cows is a significant economic and animal welfare issue in the dairy industry. The bacterial pathogens responsible for infection of the mammary gland may be split into two main categories: major and minor pathogens. Infection with major pathogens generally results in clinical illness or strong inflammatory responses and reduced milk yields, whereas minor pathogen infection is usually subclinical. Previous investigations have considered the transmission of these pathogens independently. Experimental evidence has shown cross-protection between species of pathogens. In this study a mathematical model for the coupled transmission of major and minor pathogens along with their interaction via the host was developed in order to consider various methods for controlling the incidence of major pathogen infection. A stability analysis of the model equilibria provides explanations for observed phenomena and previous decoupled modelling results. This multispecies model structure has provided a basis for quantifying the extent of cross-protection between species and assessing possible control strategies against the disease.